Benin : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2011)
This abstract discusses Benin's poverty reduction strategy (PRS1). The PRS1 serves as both a strategic frame of reference and a framework for dialogue with technical and financial partners (TFPs). The six major phases involved in the preparation of the growth and poverty reduction strategy (GPRS) and design of the macroeconomic and budgetary framework have been explained in this paper. The impact of macroeconomic and budgetary framework on the attainment of the MDGs and on the poverty reduction is also reviewed.